Assistive obstacle detection and navigation devices for vision-impaired users. - Ong, S. K.; Zhang, J.; Nee, A. Y. C. (Disability & Rehabilitation: Assistive Technology, 2013)
Quality of life for the visually impaired is an urgent worldwide issue that needs to be addressed. Obstacle detection is one of the most important navigation tasks for the visually impaired. In this research, a novel range sensor placement scheme is proposed in this paper for the development of obstacle detection devices. Based on this scheme, two prototypes have been developed targeting at different user groups. This paper discusses the design issues, functional modules and the evaluation tests carried out for both prototypes.